Excess energy in the electroexplosive nanopowders; Research on Chemical Intermediates; Vol. 36, № 6 - Yun G.-S.; Kwon Y.-S.; Kim J.-S.; Kim J.-C.; Ilyin A. P. Aleksandr Petrovich (2010, 2010)
The electroexplosive route for nanopowders production is a rapidly occurring nonequilibrium process under the action of high power density energy. The electrical explosion of conductor (EEC) powder particles have a spherical shape with protective oxide–hydroxide layer which is an adsorbed layer of working gas on the surface of particles. The formation of EEC end products (nanopowder) occurs in conditions of coexistence of metal in different states: the vapor form (cluster), plasma and superheated liquid. In this work, the formation of particles and excess energy stored during EEC were studied. Themal analysis is suggested as a method for the determination of excess energy value. According to the results of the thermal analysis, the excess energy value for nanosized aluminum powder with various storage time after passivation are 61.99–11.89 kJ/mole, respectively.